Site Specific Calibration Curve And Its Implication in The Treatment Planning of Head And Neck Cancer. - Srivastava, Roopam; Gaur, Shiva; Sharma, Pramod; Sharma, Manoj; Manjhi, Jayanand; Das, Maria; Chauhan, Dr Deepika; Sehgal, Dr Neha (JOURNAL OF ADVANCES IN PHYSICS, 2020)
Purpose: In this study, we created site specific Hounsfield Unit (HU) and Relative electron density(RED) calibration curves for computed tomography(CT) and cone beam computed tomography (CBCT) for head and neck radiotherapy dose calculation and compared them with standard calibration curves. Methods: The calibration curves between HU and RED were generated using RANDO phantom for CT and CBCT and fed in the treatment planning system for dose calculation for head and neck patients.The treatment plans for 10 head and neck cancer patients were calculated using the standard calibration curves generated with CATPHAN and head and neck calibration curves generated with RANDO phantom for both CT and CBCT. Dose accuracy of head and neck calibration curves(H/N CC) were compared to the standard calibration curves (SCC) using dose volume metrics and 3D gamma analysis. Results: The results show that slightly better dosimetric agreement from the SCC can be obtained when using this H/N CC. Conclusions: A site specific calibration curves have been proposed and tested for the head-and-neck patients and the results explain the dosimetric benefits.